The distribution of verb tenses and modals in journal articles' abstracts. Issue 3 (3rd July 2017) - Kwary, Deny A.; Kirana, Angkita; Artha, Almira F.
Abstract: This study aims at analysing the verb tenses and modals used in each sentence found in the abstracts of journal articles and explaining when each verb tense or modal is used. In addition, this study also discusses the similarities and differences in the use of verb tenses and modals across the four different disciplines, i.e. Health Sciences, Life Sciences, Physical Sciences, and Social Sciences. The study used a corpus taken from 100 abstracts of international journal articles. These journal articles are classified into four disciplines: Health Sciences, Life Sciences, Physical Sciences, and Social Sciences. The findings show that most of the sentences use the present simple and the past simple. There are also several sentences using the present perfect. Health Sciences and Life Sciences show a few sentences using the past perfect. Physical Sciences has one sentence using the present progressive. This study also found that the verbs used in Health Sciences are more numerous than the other disciplines. For modals, this study found eight modals used in the abstracts, and the modal can is the most frequently used. The results of this study are expected to assist teachers of English for Writing Academic Papers in providing more focused teaching materials.